RE-CREATION HAVEN BUILDING DESIGN FOR THE RECOVERY OF MENTAL HEALTH SYMPTOMS IN YOUNG ADULTS - Monica Sheira; Ema Yunita Titisari (Jurnal Mahasiswa Departemen Arsitektur, 2025)
Mental health issues among young adults in Malang City have shown a significant increase; however, the lack of awareness to seek professional help remains a major obstacle to recovery. This study aims to design a recreation-coping facility called Re-creation Haven as an alternative space that supports the self-recovery process of young adults. The research uses a qualitative method with a case study approach, field observations, expert interviews, questionnaires, and site surveys. The design approach is based on the healing environment concept and the operational empiricism method to explore users’ direct experiences. The study results indicate that the design of Re-creation Haven—intended as a mental recovery space for young adults—should emphasize simplicity, extensive use of natural materials, visual friendliness, abundant vegetation, and various recreational activities, all in accordance with the characteristics of the healing environment concept. Re-creation Haven offers an alternative spatial concept that integrates recreation and psychological healing elements, addressing the need of young adults for a safe and comfortable place for independent recovery.